Bidirectional SSB modulation for Hybrid-PON with source-free optical network units - Zhang, Xiaoling (2018)
A bidirectional single-side band (SSB) modulation based passive optical network (PON) with source-free optical network units (ONUs) is proposed, where orthogonal frequency division multiple based carrierless amplitude and phase (OFDM-CAP) is employed in the downstream while wavelength division multiplexing (WDM) is utilized in the upstream.